SYNTHESIS AND PROPERTIES OF ETHANOLAMIDES ACIDS OF HIGLYERUCIC RAPESEED OIL - Bodachivskyi, Iuriy; Bilokopytov, Iuriy; Pop, Grigoriy (Proceedings of National Aviation University (archive), 2014)
First are synthesized a series of surface-active substances (surfactants) by transamidation of high erucic rapeseed oil with mono- and diethanolamines. Due to the specific composition of initial oils and products on their basis, the synthesized surfactants are characterized by multifunctional properties and can be used for creation of effective emulsion-suspension systems for petroleum refineries and lubricants with improved antioxidant, anticorrosion, anti-wear and extreme pressure characteristics